THEiINFLUENCE OFiORGANIZATIONAL CULTUREiAND ORGANIZATIONAL COMMITMENTiON WORKiSTRESS LEVELS OF MAKASSAR TOURISM DEPARTMENT EMPLOYEES - Asfira Nengsi; H Djabir Hamzah (Scientia Integritas Utama, 2023)
Thisistudy aimsito investigate howiorganizational cultureiand organizationalicommitment affect the level of work stress of Makassar City Tourism Office employees. This study used a quantitativeimethod withia populationiof all Creative Economy Employees at the Makassar City Tourism Office and a sample of 50 respondents. Dataiwere collectedithrough observation, questionnaires, andiinterviews, andiwere analyzediusing multipleilinear regression methods with the help of SPSS IBM 16. Theiresults showedithat organizational cultureivariables partially hadia positiveiand significantieffect onithe level of employee work stress. However, the organizational commitment variable only has a positive effect without having aisignificant effection the level of employee work stress. Overall, organizational cultureiand organizationalicommitment togetheriinfluence employee stress levels.